Implementation of Deep Breathing Relaxation to Manage Acute Pain in Dyspepsia Patients in the Internal Ward of Serui Regional General Hospital (PT. LARPA JAYA PUBLISHER, 2025)
Dyspepsia is a common digestive disorder characterized by symptoms such as epigastric pain, nausea, and vomiting. Its prevalence in Indonesia reaches 40–50% and it is a leading cause of hospitalization. Acute pain in dyspepsia often affects patients’ quality of life, thus requiring appropriate nursing care. This case study applied a nursing process approach, including assessment, diagnosis, intervention, implementation, and evaluation, to provide care for a dyspepsia patient experiencing acute pain, aiming to reduce complaints and improve comfort. Data were collected through interviews, observations, and physical examinations on February 24–25, 2025, at Serui Regional General Hospital. The data analysis concluded that effective communication skills were essential during assessment, nursing diagnoses were tailored to the patient’s condition, and the diagnoses identified included acute pain, nausea, nutritional imbalance, and knowledge deficit. The primary priority was acute pain, managed through pain management interventions, resulting in decreased pain levels. The acute pain issue was resolved on the first day, achieving the desired goals and outcome criteria. Nursing care provided to patient Nn. R.T successfully addressed the acute pain problem.